Investigating the Causes of Undue Financial Balance for Removal of Internal Fixator under the Tw-DRGs Payment System - Shuo-Po Weng; Yu-Ling Wu; Jen-Yu Chen; Yu-Han Lo; Chien-Jen Hsu (Formosan Journal of Musculoskeletal Disorders)
Background: According to data from Kaohsiung Veterans General Hospital (KSVGH), 67.9% of patients undergoing internal fixator removal incurred a negative financial balance. Objectives: We conducted this retrospective study to investigate factors contributing to such a negative financial balance to policy recommendations for addressing profit loss. Materials and Methods: We retrospectively collected the data of patients hospitalized for internal fixator removal between January 2019 and August 2020 from the KSVGH clinical database. The data included patient demographic characteristics, emergency records, surgical records, hospitalization records, and declarations of expense from the National Health Insurance Administration. Results: The fees for surgery, anesthesia, and use of ward beds constituted over 80% of the total cost. Patients with two or more procedural codes incurred a negative financial balance; however, 65.4% of patients with a single procedural code had a negative financial balance. The average cost of general anesthesia (NT$7150) was nearly twice that of spinal anesthesia (NT$3675). Among patients undergoing implant removal at two sites of the same upper extremity, the use of regional anesthesia instead of general anesthesia in 23 patients would have saved NT$57,523, and the use of a brachial plexus nerve block instead of general anesthesia in 16 patients would have saved NT$111,808. When brachial plexus block anesthesia was used, patients can leave the hospital 6 h after surgery. Under the Taiwan Diagnosis-Related Group payment system, additional procedural codes did not increase the profit of the hospital. Reporting two or more procedural codes engendered a negative financial balance. Conclusions: Either spinal anesthesia or brachial plexus block anesthesia could reduce medical expenses for patients undergoing internal fixator removal at two sites of the same extremity. Registering two or more procedural codes was noted to engender a negative financial balance.